An integrated seismic and well data study of shallow fluid accumulations in Snøhvit, SW Barents Sea - Arntzen, Andreas (UiT The Arctic University of Norway, 2018)
In the vicinity of the Snøhvit hydrocarbon reservoir in the Hammerfest Basin a number of fluid flow phenomena occur, e.g. free gas accumulations, pockmarks and potential indicators of gas hydrates.The presence of shallow gas may cause major blowouts during drilling. To reduce the risk, it is important to locate the shallow gas and gas hydrates. CO2 has been injected into the Snøhvit reservoir since 2008, even though there has been proven leakage from the reservoir. Leakage of CO2 from the reservoir, through the overburden reaching the seabed is a significant environmental risk. Therefore, it is important obtain a detailed understanding to processes controlling fluid flow, how deep-seated faults can act as conducts for fluid migration, as well as the origin of the shallow gas and gas hydrates located above the reservoir. Newly released 3D seismic data shows the upper few 100s meters of the overburden at Snøhvit in much more detail than previous known, due to reprocessing. In this thesis the migration mechanisms of fluids are described in detail together with seismic indications of shallow gas and gas hydrates. Further, pockmarks, gas chimneys and high amplitude anomalies were mapped out and discussed in relation to deep seated faults penetrating the reservoir. A conceptual model was carried out explaining the origin of the shallow gas above the Snøhvit field in relation to the geological history in the area and how faults play an important part. It was found that the cycles of glacial loading and unloading during the Cenozoic have caused extensive fracture developments, leading to migration of gas from the reservoir to form shallow accumulations of gas and gas hydrates with suitable pressure and temperature conditions. A simpe analytical model was used to determine the leak off factor of two faults located close to the F-2 CO2 injector, and to study which parameters might affect the migration of CO2 from the reservoir through a faoult and into overlying sand, thereby explore more about the risk of storing CO2 in ...